A survey of quiet auroral arc orientation and the effects of the interplanetary magnetic field. Issue 4 (4th April 2014) - Gillies, D. M.; Knudsen, D. J.; Donovan, E. F.; Spanswick, E. L.; Hansen, C.; Keating, D.; Erion, S.
<x xml:space="preserve">Abstract</x> Using data from the THEMIS All‐Sky Imager array, we have carried out an extensive study of the orientation of quiet auroral arcs relative to the magnetic east‐west direction. We used over 7500 images of quiet auroral arcs that were collected during extended solar minimum and at various geomagnetic latitudes and longitudes. For each arc, we determined its "tilt" (the angle the arc makes with the local magnetic east‐west direction) and its "multiplicity" (whether or not the arc was part of a multiple‐arc system). We have found that at more equatorward latitudes, arc tilts are within σSD = ±7.7∘. We determined that both single‐ and multiple‐arc systems tend to tilt a few degrees to the south‐east prior to 23 magnetic local time (MLT) and to the north‐east afterward. This tilt appears to be more prominent at higher latitudes. We compared the auroral arc orientations to the mapping of equatorial contours of constant magnetic field strength into the ionosphere, where we used the T87 and T89 magnetic field models for quiet (Kp = 1, 3) conditions for the mappings and to determine the constant equatorial magnetic field strength contours. We found that the MLT trends of the tilts are such that arc alignment appears to follow the constant magnetic field strength contours as projected into the ionosphere. We assert that the systematic dependencies of the orientation of auroral arcs indicate that arc morphology is governed by the large‐scale structure of the magnetosphere as opposed to localized processes within the ionosphere. In addition, we studied the effects of the interplanetary magnetic field (IMF) on the location in MLT of the reversal of the arc tilts. We found that negative IMF Bxand Byconditions cause the reversal location to shift duskward of 23 MLT. Alternately, a positive IMF Bx, coupled with a negative By, results in a shift in reversal location toward magnetic midnight. This behavior is consistent with that found in studies of the MLT distribution of substorm onsets.